2017
DOI: 10.1080/03650340.2017.1352087
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in the rhizosphere of Phragmites australis from an oil-polluted wetland

Abstract: Although Phragmites australis is commonly planted in constructed wetlands, very little is known about its roots-associated bacterial communities, especially in wetlands used for the remediation of oil produced waters. Here, we describe the bacterial diversity, using molecular (illumina MiSeq sequencing) and cultivation techniques, in the rhizosphere soils of P. australis from an oil-polluted wetland in Oman. The obtained isolates were tested for their plant-growth promoting properties. Most sequences belonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…The strain collection obtained from P. australis rhizosphere in this study was dominated by Firmicutes (57% of the isolates), with a lower percentage of Proteobacteria and Bacteroidetes, that found a more suitable habitat in the plant endosphere, and Actinobacteria , that conversely were not isolated from the endosphere fraction. Previous studies, in contrast with our results, by applying cultivation-independent Next Generation Sequencing approaches retrieved in the rhizosphere of P. australis the dominance of the phylum Proteobacteria [50,51,52]. The dominance of Firmicutes in our collection could be a cultivation-related bias, although we have to consider that the plant species is not the only factor that modulates the bacterial community structure in the root apparatus, acting together with different abiotic factors [53] and making reasonable that the rhizosphere community of P. australis collected from CW systems treating different wastewaters hosts specific peculiar gram positive taxa.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The strain collection obtained from P. australis rhizosphere in this study was dominated by Firmicutes (57% of the isolates), with a lower percentage of Proteobacteria and Bacteroidetes, that found a more suitable habitat in the plant endosphere, and Actinobacteria , that conversely were not isolated from the endosphere fraction. Previous studies, in contrast with our results, by applying cultivation-independent Next Generation Sequencing approaches retrieved in the rhizosphere of P. australis the dominance of the phylum Proteobacteria [50,51,52]. The dominance of Firmicutes in our collection could be a cultivation-related bias, although we have to consider that the plant species is not the only factor that modulates the bacterial community structure in the root apparatus, acting together with different abiotic factors [53] and making reasonable that the rhizosphere community of P. australis collected from CW systems treating different wastewaters hosts specific peculiar gram positive taxa.…”
Section: Discussioncontrasting
confidence: 99%
“…Root biomass improvement is of paramount importance for the macrophytes used in CW systems since it has the potential to result in an improved filtration and reduced flow velocity of wastewaters, besides offering a higher surface and more extended habitat for the colonizing microbial community [57]. As shown in other studies performed on P. australis , a high percentage of bacteria isolated from both endosphere and rhizosphere was able to produce IAA and exhibited ACC deaminase activity [47,52], showing a significant potential of P. australis microbiome in sustaining plant adaptation and growth under the stressed conditions of a CW system.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial consortia of many wetland plants' roots have been investigated via culture-dependent and molecular methods (Jiang et al, 2013;Li et al, 2013;Abed et al, 2018). The era of highthroughput genomic technologies accelerated the discovery of root zones microbes as well as their biological activities.…”
Section: Microbial Consortia Associated With Phragmites Australis In Environmental Remediationmentioning
confidence: 99%
“…However, the knowledge of the microbial consortia of the reed's rhizosphere in oil-polluted wetlands is still minimal. Abed et al (2018) reported bacterial communities in the rhizosphere of the reed from an oil-polluted wetland using molecular (Illumina MiSeq sequencing) and culture-based methods, and showed that the dominant phyla belonged to Proteobacteria, Bacteriodetes, and Firmicutes.…”
Section: Microbial Consortia Associated With Phragmites Australis In Environmental Remediationmentioning
confidence: 99%
“…The microbial communities in the sediments, soils and rhizospheres of various wetlands that are associated with different specific characteristics and functions have been explored extensively [2,5,27,28]; however, studies on the microbial communities in wetland waters remain limited [29]. In the current study, we investigated the planktonic microbial community in an artificially irrigated estuarine wetland and its receiving river as well as the responses of the community to environmental parameters.…”
Section: Distinct Seasonal Dynamics Of Planktonic Bacterial and Archamentioning
confidence: 99%